Cephalometric evaluation of the relationship between cervical vertebral morphology and anomalies and the cranial base angle in different facial types and skeletal classes = Evaluación cefalométrica de la relación entre la morfología vertebral cervical y las anomalías y el ángulo de la base del cráneo en diferentes tipos faciales y clases esqueléticas - Ostovarrad, Farzaneh; Faghani, Masoumeh; Yousefi, Zahra; Tadayoni, Zahra; Tofangchiha, Maryam (2024)
This study examines the morphology and common anomalies of the cervical vertebrae in different skeletal classes and facial types. This cross-sectional study was conducted on 137 lateral cephalometric images of patients aged 18-55 years. The images were evaluated for fusion and posterior arch deficiency as the two most common anomalies along with cervical vertebral morphology (dense angle, the height of the posterior arch of the atlas, the external anterior posterior diameter of the atlas, and the cranial base angle). Data were categorized into three skeletal classes based on the Wits analysis and the ANB angle and also three facial types based on the SN-MP angle. These calculations were performed in SPSS 22 at the significance levelof P<0.05. The height of the posterior arch of the atlas was directly and significantly related to age and increased with it. The mean external anterior posterior diameter of C1 was higher in men and in the hypodivergent group. As for the other factors, including cervical spine anomalies, no significant relationship was observed with age, sex, skeletal classes, facial types, and the cranial base angle. Moreover, the mean morphology of the cervical spine was not significantly associated with skeletal classes. Based on the results, the height of the posterior arch of the atlas was associated with age and increased along with it. Moreover, the mean external anterior posterior diameter of the atlas was greater in men and in hypodivergent individuals.
Este estudio examina la morfología y anomalías comunes de las vértebras cervicales en diferentes clases esqueléticas y tipos faciales. Este estudio transversal se realizó en 137 imágenes cefalométricas laterales de pacientes de 18 a 55 años. Las imágenes fueron evaluadas para detectar fusión y deficiencia del arco posterior como las dos anomalías más comunes junto con la morfología vertebral cervical (ángulo denso, la altura del arco posterior del atlas, el diámetro anterior externo posterior del atlas y el ángulo de la base del cráneo). Los datos se clasificaron en tres clases esqueléticas según el análisis de Wits y el ángulo ANB y también en tres tipos faciales según el ángulo SN-MP. Estos cálculos se realizaron en SPSS 22 con un nivel de significancia de P<0,05. La altura del arco posterior del atlas estaba directa y significativamente relacionada con la edad y aumentaba con ella. El diámetro anteroposterior externo medio de C1 fue mayor en los hombres y en el grupo hipodivergente. En cuanto a los demás factores, incluidas las anomalías de la columna cervical, no se observó una relación significativa con la edad, el sexo, las clases esqueléticas, los tipos faciales y el ángulo de la base del cráneo. Además, la morfología media de la columna cervical no se asoció significativamente con las clases esqueléticas. Según los resultados, la altura del arco posterior del atlas se asoció con la edad y aumentó con ella. Además, el diámetro anteroposterior externo medio del atlas fue mayor en hombres y en individuos hipodivergentes.
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 14 de febrero, 2025
También disponible en formato HTML y EPUB